The school is not a company, nor education a business - Deyby Rodrigo Espinosa Gómez (Corporación Universitaria Minuto de Dios, 2017)
This article proposes a critical reflection on the influence of business discourse in the school, which considers education as an essentially private good and whose value is above all economic. Today, concepts such as "quality", "competences", "indicators", "excellence", "standards", "performance evaluation", "standardized tests" 'Supply and demand', 'customer and service', etc., which belong to business, are attached to education. This has made this type of concepts to be overestimated and not education itself; that is, business concepts are used as a generic expression and as the only truth to characterize education. In this sense, first, the traps, effects and consequences of one of the original concepts of the business world will be exposed, as is the quality of education. Secondly, there arises the need and urgency to unveil alternative practices in defense of the school, as institution, that recovers education as a social value.